Dissection of Closely Linked Quantitative Trait Locis Controlling Grain Size in Rice - Xue, Pao; Chen, Yu-yu; Wen, Xiao-xia; Wang, Bei-fang; Yang, Qin-qin; Gong, Ke; Kang, Yi-wei; Sun, Lian-ping; Yu, Ping; Cao, Li-yong; Zhang, Ying-xin; Zhan, Xiao-deng; et al. (Frontiers in Plant Science, 2022)
Grain size is a key constituent of grain weight and appearance in rice. However, insufficient attention has been paid to the small-effect quantitative trait loci (QTLs) on the grain size. In the present study, residual heterozygous populations were developed for mapping two genetically linked small-effect QTLs for grain size. After the genotyping and the phenotyping of five successive generations, qGS7.1 was dissected into three QTLs and two were selected for further analysis. The qTGW7.2a was finally mapped into a 21.10 kb interval containing four annotated candidate genes. Transcript levels assay showed that the expression of the candidates LOC_Os07g39490 and the LOC_Os07g39500 were significantly reduced in the NIL-qTGW7.2aBG1. The cytological observation indicated that qTGW7.2a regulated the grain width through controlling the cell expansion. Using the same strategy, qTGW7.2b was fine-mapped into a 52.71 kb interval containing eight annotated candidate genes, showing a significant effect on the grain length and width with opposite allelic directions, but little on the grain weight. Our study provides new genetic resources for yield improvement and for fine-tuning of grain size in rice.